The Influence Of Regional Original Revenue On Capital Expenditure In Regencies/Cities Of North Sumatera - Siti Arifah; Ayu Kurnia Sari; Dito Aditia Darma Nst (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
Regional expenditure constitutes financial outlays undertaken by subnational governments (at provincial, regency, or city levels) to fund diverse programs, projects, and activities designed to fulfill societal requirements and execute governmental responsibilities at the local tier. This expenditure encompasses considerable budgetary provisions allocated toward critical sectors including education, health services, infrastructure development, security apparatus, public service delivery, and related domains. The budgetary allocation framework for regional expenditure comprises revenues generated from local sources, intergovernmental transfer mechanisms from the central authority, and supplementary financial resources. These fiscal resources are deployed to support prioritized initiatives and ventures delineated within regional development strategies.The empirical evidence further reveals that jurisdictions demonstrating sustained enhancement in locally-generated revenues exhibit enhanced fiscal sustainability, consequently diminishing reliance upon centrally-administered transfer allocations. However, notable fiscal asymmetries persist across territorial units. Certain regencies and municipalities characterized by modest local revenue generation demonstrate a propensity to dedicate diminished proportions toward capital investment while maintaining heightened dependency on recurrent operational expenditures. The regression analysis yields a positive coefficient estimate for the local revenue variable, exhibiting statistical significance at p < 0.05, thereby indicating that incremental growth in local own-source revenue corresponds with proportional increases in capital expenditure allocation.